Psikoedukasi sebagai Upaya Preventif Cyberbullying pada Siswa SMA - Hastuti, Rahmah; Johan, Hani Rahmawati; Nguru, Marcia Vinly Calysta (Universitas Pahlawan Tuanku Tambusai, 2026)
This Community Service Activity (CSA) aims to enhance high school students' understanding of cyberbullying thru psychoeducation as a preventive measure. The activity was conducted at SMA Negeri X Jakarta, involving 112 students. The methods used include material presentation, interactive discussions, reflective games, QA sessions, and evaluation thru questionnaires. The material focuses on introducing forms of cyberbullying, its impact on the psychological and social conditions of adolescents, and prevention strategies thru empathy, positive communication, and wise use of social media. The evaluation results showed a positive response from the participants, with 72.3% of students rating the material as very good and 61.6% rating the interaction with the resource person as very good. This activity shows that psychoeducation can be a relevant means to enhance students' awareness, empathy, and readiness to prevent cyberbullying in the school environment.